Formulasi Dan Uji Aktivitas Antipiretik Plester Hidrogel Ekstrak Etanol Daun Kelor (Moringa oleifera Lam) - Mayrini Zuria, Debi Meilani (Journal of Health and Medical Science, 2022)
Fever can be defined as a state of body temperature above normal more than 37.5 oC. Fever is characterized as a symptom of infectious and non-infectious diseases. One way to reduce fever with traditional medicine is the Moringa plant. Moringa plant (Moringa oleifera Lam.) which contains flavonoid compounds is known to be efficacious as a fever reducer. This study aims to determine the formulation of the ethanolic extract of Moringa leaves (Moringa oleifera Lam.) in hydrogel plaster as a fever reducer. This research method includes simplicia characterization, phytochemical screening, and extraction by maceration. The extract was made in three hydrogel formulations as a fever-reducing plaster with a composition of every 30 g of preparation containing 5 g (FI), 7.5 g (FII), and 10 g (FIII) leaf extract. The tests carried out included organoleptic tests, pH tests, viscosity tests, homogeneity tests and temperature reduction tests on test animals. From the research results, the data were analyzed using SPSS with ANOVA test followed by Tukey's test. The results of the three Moringa leaf extract hydrogel formulas, namely FI, FII and FIII have the same characterization, namely semi-solid form, distinctive odor and brown color, hydrogel pH 5.0-6.5, viscosity 35380-93920 cP and homogeneous. The results of the decrease in body temperature of mice showed that FIII was the most effective in reducing the body temperature of mice with a time of 60 minutes.